Emotion-centered and action-centered coping in elite sport: Task execution design approach - Hanin, Y.; Hanina, M.; Sašek, H.; Kobilšek, A. (International Journal of Sports Science & Coaching, 2016)
Task execution design approach to optimization of athletic performance aims to help elite athletes and coaches to prevent underperformance in competitions. This individual-specific coping framework includes: (i) constraints-led competition environment; (ii) appraisals, (iii) decision making, and (iv) emergent performance patterns. Practical utility of the Task execution design approach is illustrated by a five-year participant observation case study involving an elite female shooter, her coach, and two consultants. This longitudinal study describes a systematic cooperation that identified several practical problems in competition, with a special reference to the athlete`s transition from juniors` to seniors` category. The athlete developed three effective coping strategies: emotion-centered, action-centered, and combined (plans A, B, and C). These strategies were used depending on performer-environment relationship in the framework of ecological dynamics. The study shows how the athlete`s needs in self-control changed during five years and were satisfied using the proposed Task execution design framework. The main emphasis was on the qualitative analysis of the experiential knowledge based on the athlete`s and coach`s self-perceptions and self-reflections. The case also illustrates how the athlete and her coach used the RLD and ALD principles in their preparation for competition. The validity of the Task execution design approach was tested by the practitioners across 14 different sports. ABSTRACT FROM AUTHOR